Hydrothermal Synthesis and Crystal Structure of Cd(II) Coordination Polymer - Li, Bin (Asian Journal of Chemistry, 2013)
One new cadmium compound [Cd(L)]·(bip)n(1) [H2L = 5-hydroxyisophthalic acid and bip = 1,5-bis(2-methyl-imidazol-1-yl) pentane] has been successfully synthesized. Compound shows a two-dimensional frameworks. The bip ligands are filled the hole of 2D layer.